The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/su13020511
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Soil Heavy Metal Sources in a Large-Scale Area Affected by Industry

Abstract: Heavy metals (HMs) in soil are some of the most serious pollutants due to their toxicity and nonbiodegradability. Especially across large-scale areas affected by industry, the complexity of pollution sources has attracted extensive attention. In this study, an approach based on zoning to analyze the sources of heavy metals in soil was proposed. Qualitative identification of pollution sources and quantification of their contributions to heavy metals in soil are key approaches in the prevention and control of he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…Lower soil Cd in the present study than that in Shanxi Province, China and Central Greece can be observed [1], which might result from long-term agricultural activities, such as the application of agrochemicals and fertilizer in Shanxi Province and Central Greece [33]. Cu was more obviously accumulated in some sites (DM soils, T1 soil, and KQ soil) than in other studies [1,32], but concentrations of Pb in DM, TM, and DDS soils were lower than that in Hunan Province (97 mg/kg) [31]. Se, Mo, and Mn are not listed in the soil quality standard of China, but their concentrations were comparable to the background values of soil (except Se in KQ soil), indicating a lower environmental risk.…”
Section: Heavy Metal(loid)s In Soilsmentioning
confidence: 78%
See 1 more Smart Citation
“…Lower soil Cd in the present study than that in Shanxi Province, China and Central Greece can be observed [1], which might result from long-term agricultural activities, such as the application of agrochemicals and fertilizer in Shanxi Province and Central Greece [33]. Cu was more obviously accumulated in some sites (DM soils, T1 soil, and KQ soil) than in other studies [1,32], but concentrations of Pb in DM, TM, and DDS soils were lower than that in Hunan Province (97 mg/kg) [31]. Se, Mo, and Mn are not listed in the soil quality standard of China, but their concentrations were comparable to the background values of soil (except Se in KQ soil), indicating a lower environmental risk.…”
Section: Heavy Metal(loid)s In Soilsmentioning
confidence: 78%
“…Notes:1 Coefficient variation, 2 Date from reference[1],3 Date from reference[31],4 Date from reference[32],5 Background values of soil heavy metal(loid)s in Heilongjiang province[22],6 Date from reference[30].…”
mentioning
confidence: 99%
“…The reason for the high content of heavy metals can be attributed to human activities. At the same time, researchers analyzed the spatial distribution characteristics, sources, and input pathways of heavy metals in soils based on principal component analysis (PCA) (Ustaoglu and Islam, 2020), positive matrix decomposition (PMF) (Xu et al, 2021), cluster analysis (CA) (Kelepertzis, 2014), geographic information systems (GIS) (Anaman et al, 2022), indicators such as contamination factors (CF) (Marrugo-Negrete et al, 2017;Baltas et al, 2020), geologic enrichment index (I-geo) (Islam et al, 2015;Adimalla, 2020), and potential ecological risk (PERI) (Maanan et al, 2015;Kusin et al, 2018). The application of those integrated methods can help to identify the sources and transport routes of heavy metals under different land-use patterns, and provide more reliable data for ecological risk assessments.…”
Section: Introductionmentioning
confidence: 99%
“…But the most dangerous factor for plants and other living organisms is the degree of accessibility, which is determined by the mobility of chemical elements [6]. Heavy metals (HM) in soil are one of the most serious pollutants due to their toxicity and nonbiodegradability [7]. Heavy metals are involved in biological circulation, are transferred along food chains and cause a number of negative consequences.…”
Section: Introductionmentioning
confidence: 99%